Analysis of hydraulic sectorization in water distribution networks implementing Epanet and iDistritos (BISTUA Revista de la Facultad de Ciencias Básicas, 2023)
The primary purpose of drinking water distribution networks is to supply drinking water to meet a population's quantity and quality needs. These systems are designed to continuously supply water to all inhabitants throughout the day. These optimal operating conditions in some cities are not achieved due to different problems that affect the regular operation of the distribution networks. This research presents a proposal to improve and optimize the hydraulic networks of the city of Los Patios, located in Norte de Santander, Colombia. This city currently presents problems in the operation of its distribution system due to population growth, informal settlements, lack of planning in constructing its pipe networks and water availability in the supply source. The current operation of the network is carried out by closing sectioning valves in order to generate sectors and thus guarantee service shifts that provide water by zones between two to three days a week, which does not comply with the service continuity criteria and affects the quality of the resource; in response to this problem, this research proposes several alternatives for hydraulic sectorization of the pipe networks using graph theory and the iDistricts and Epanet software. As a result, an optimization of the hydraulic operation of the distribution network was obtained, increasing the continuity of the service, and the actions and recommendations necessary to develop these alternatives are described.
Keywords: Water distribution systems; Graph Theory; Hydraulic Sectorization; Epanet; iDistricts